Hw8webworksolutions - terms y = 2 e 2 x 7 cos x 7 y-1 7 8 Find dy/dx if ln xy = e x y Answer Again I use implicit differentiation d dx(ln xy = d

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Everybody is assigned slightly different versions of each problem. The below are representative examples of the assigned problems, but may not exactly match the problem you were assigned. 1. Use implicit differentiation to find dy/dx , given: e 2 x = sin( x + 7 y ) . Answer: First, differentiate both sides with respect to x : d dx ( e 2 x ) = d dx (sin( x + 7 y )) e 2 x · 2 = cos( x + 7 y ) · d dx ( x + 7 y ) 2 e 2 x = cos( x + 7 y ) · (1 + 7 y 0 ) by the Chain Rule, or, equivalently, 2 e 2 x = cos( x + 7 y ) + 7 y 0 cos( x + 7 y ) . Isolating the y 0 term yields 7 y 0 cos( x + 7 y ) = 2 e 2 x - cos( x + 7 y ) , so we have y 0 = 2 e 2 x - cos( x + 7 y ) 7 cos( x + 7 y ) . This would be a perfectly acceptable answer, or I could also split the right hand side into two
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: terms: y = 2 e 2 x 7 cos( x + 7 y )-1 7 . 8. Find dy/dx if ln( xy ) = e x + y . Answer: Again I use implicit differentiation: d dx (ln( xy )) = d dx ( e x + y ) 1 xy · d dx ( xy ) = e x + y · d dx ( x + y ) 1 xy ( xy + 1 · y ) = e x + y (1 + y ) xy xy + y xy = e x + y + y e x + y y y + 1 x = e x + y + y e x + y . 1 Grouping the terms containing y yields y ± 1 y-e x + y ² = e x + y-1 x , so we see that y = e x + y-1 x 1 y-e x + y . 2...
View Full Document

This note was uploaded on 01/18/2012 for the course MATH 2250 taught by Professor Chestkofsky during the Fall '08 term at University of Georgia Athens.

Page1 / 2

Hw8webworksolutions - terms y = 2 e 2 x 7 cos x 7 y-1 7 8 Find dy/dx if ln xy = e x y Answer Again I use implicit differentiation d dx(ln xy = d

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online